Vom Hündlein der Siebenschläfer: Goethe und Rückert in der Aneignung orientalischer Überlieferung = On the Dog of the Seven Sleepers: Goethe and Rückert in the Appropriation of an Oriental Tradition - Quatrale, Marta (Zeitschrift für Religions- und Geistesgeschichte, 2026)
This essay argues that the figure of the dog (Kitmīr/Qitmir) in the Seven Sleepers tradition serves as a test case for poetic and conceptual regimes in early nineteenth- century German reception. Reading Johann Wolfgang von Goethe’s West-östlicher Divan and Friedrich Rückert’s Ein Hündlein, das einst Wache that bei Schäfern … (published in the Taschenbuch für Damen, 1822, in the same context that also produced the Östliche Rosen) alongside Qurʾān 18, Ṭabarī, Ṯaʿlabī, Hammer’s versified Qurʾān and Claudius James Rich in Fundgruben des Orients, as well as Gregory of Tours and Jacob of Serugh, the study shows how Goethe aestheticizes and stabilizes doctrinal tensions, whereas Rückert elevates the creature within a mediating, barzakh-like framework. The comparison tracks a shift from ornamental adaptation to transformative re-coding and locates key pressure points in seemingly marginal narrative details. The case sheds light on broader patterns in German engagements with Sufi metaphysics between 1800 and 1850.